ELECTRONIC TRADE IN THE CONDITIONS OF INTERNATIONAL ECONOMIC ACTIVITY - KOVTUN, EDUARD (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In recent years, global digitalization has led to a fairly active development of e-commerce, which has become an integral part of the global retail system. As in other industries, retail has undergone significant changes since the advent of the World Wide Web, and today's dynamic pace of modern life has benefited consumers from virtually all over the world from the benefits of online transactions.The article examines the essence, characteristics, advantages and problems of e-commerce as a new form of economic relations of business entities in the global trading system. The current state and dynamics of e-commerce development in the world are analyzed. The world's leading global and national companies, countries and e-commerce markets have been identified.
Keywords: trade policy; international trade; e-commerce; internet networks; e-business; e-commerce market; trade and economic activity